From fields to factories: Special economic zones, foreign direct investment, and labour markets in Vietnam - Tevin Tafese; Jann Lay; Van Tran (German Institute of Global and Area Studies (GIGA), 2023)
Vietnam has integrated into global value chains through the establishment of special economic zones (SEZs). This paper examines the local labour-market impacts of this programme, building on a unique dataset of SEZs in combination with labour force survey (LFS) data. Using historical satellite imagery, we trace the built-up area of SEZs over time to construct a continuous measure of SEZ exposure, which we link to the LFSs at the districtyear level for 2013-2019. In a difference-in-differences design with continuous treatment, we find that SEZs have led to a rapid shift in employment from agriculture and services to manufacturing and to an improvement in the quality of employment through higher wages and more formal employment. Foreign firms drive these effects, but there are positive spillovers to workers in domestic firms in agriculture and services. The effects are particularly strong for women, and younger individuals with low and medium levels of education.
Keywords: J23; J24; J30; J80; O14; O17; O19; P33; 330; Vietnam; Special Economic Zones; foreign direct investment; labour markets; structural change; informality